1954
DOI: 10.1084/jem.100.3.225
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Structure of Steroids in Relation to Promotion of Growth of the Vagina and Uterus of the Hypophysectomized Rat

Abstract: In the hypophysectomized albino rat which is protected from contact with steroids in the ration and environment the uterus and vagina are highly atrophic but are sensitive indicators of activity of substances which promote their growth. Both the pituitary growth hormone and certain steroids have the common property of inducing growth of these tissues. The vaginal epithelium consists of 2 layers of cells which differ profoundly in their growth in response to steroids, depending on the molecular s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
1

Year Published

1957
1957
2010
2010

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(21 citation statements)
references
References 14 publications
1
19
1
Order By: Relevance
“…5 androstene-3 ,17 -diol (5-Adiol) has estrogenic activity in rats (Huggins et al, 1954) and binds to the ER in rat uterus (Garcia and Rochefort, 1979). Kuiper et al (1997) reported that 5Adiol has nM affinity for recombinant ER and ER .…”
Section: A Paradox the Er And Not The Pr Is Most Ancient: What Was Tmentioning
confidence: 99%
“…5 androstene-3 ,17 -diol (5-Adiol) has estrogenic activity in rats (Huggins et al, 1954) and binds to the ER in rat uterus (Garcia and Rochefort, 1979). Kuiper et al (1997) reported that 5Adiol has nM affinity for recombinant ER and ER .…”
Section: A Paradox the Er And Not The Pr Is Most Ancient: What Was Tmentioning
confidence: 99%
“…1) (Baker 2001a). For example, 5 -androstenediol has long been known to have estrogenic activity (Huggins et al 1954) and to bind to the ER (Garcia & Rochefort 1979). Kuiper et al (1997) showed that 5 -androstenediol and 3 -androstanediol bind to recombinant rat ER and ER with nanomolar affinity.…”
Section: Introductionmentioning
confidence: 99%
“…oestrogenic effects in the rat (Huggins et al, 1954), and more recently that, at concentrations found in the blood of Western women, it both increased uterine growth and DNA synthesis in this species (Seymour-Munn and Adams, 1983). Because of the androgenic origins of this oestrogen-like compound it has been dubbed 'hermaphrodiol' by Adams (1983).…”
Section: Discussionmentioning
confidence: 99%